Method for selecting ornamental species for different shading intensity in urban green spaces - Francini, Alessandra; Toscano, Stefania; Ferrante, Antonio; Romano, Daniela (Frontiers in Plant Science, 2023)
In urban areas, ornamental plants face different constraints, such as the shading of buildings and trees. Therefore, the selection of suitable species and their integration or combination with pre-existing plants is very important. Trees, shrubs, and herbaceous plant species must be distributed according to plant light requirements and shading intensity. Ornamental plants are classified into two groups based on their light intensity or shade tolerance: sun and shade species. To properly position the plants, especially in the immediate vicinity of buildings, it is necessary to study the projection of shadows during the year and the most critical periods, such as July and August. The position of ornamental species with different shading tolerances can be obtained by characterizing the leaf gas exchange for each species. Among the physiological parameters, the most important is the light compensation point, which is the light intensity corresponding to a net photosynthesis equal to zero. This means that the assimilation of carbon dioxide through photosynthesis is equal to the carbon dioxide emitted by respiration. This steady state represents the most critical condition for plants to endure the summer. The distribution of species inside a green area should be determined by considering the minimum light intensity that allows sufficient photosynthesis to compensate for the respiration rate. In this context, non-destructive leaf gas exchange, chlorophyll a fluorescence, and chlorophyll content can be useful tools for selecting suitable ornamental plants under diverse shading conditions.